Unilateral versus bilateral sinonasal disease: Considerations in differential diagnosis and workup. (20th June 2019) - Eckhoff, Austin; Cox, Daniel; Luk, Lauren; Maidman, Samuel; Wise, Sarah K.; DelGaudio, John M.
Abstract : Objective: Imaging findings play an important role in the workup and diagnosis of sinonasal disease. Unilateral versus bilateral involvement is a key finding that can differentiate between various diagnoses. Our objective is to characterize presenting symptoms, imaging findings, and most common diagnoses associated with unilateral versus bilateral sinonasal disease. Methods: Patients who underwent surgical intervention for sinonasal disease at Emory University between May 2015 and December 2016 were included in the study. Information including demographic variables, comorbidities, presenting symptoms, imaging findings, and pathologic diagnosis was collected for each patient. Unilateral versus bilateral disease was determined by preoperative computer tomography and magnetic resonance imaging, and correlated to surgical and pathologic findings. Data was analyzed using quantitative methodologies and descriptive statistics. Results: The study cohort consisted of 250 patients presenting for primary sinonasal surgery, including 110 patients with unilateral disease and 140 patients with bilateral disease. The most common diagnosis for patients with bilateral disease was chronic rhinosinusitis with nasal polyps (46%) followed by chronic rhinosinusitis without polyps (26%). For patients with unilateral disease the most common diagnoses were chronic rhinosinusitis without nasal polyps (21%), malignancy (19%), benign neoplasm (15%), and allergic fungal sinusitis (10%). There was a statistically significant association between unilateral sinonasal disease and the final diagnosis of benign neoplasm (OR = 7.8, P < .01) and malignancy (OR = 8, P < .01). Conclusion: Patients with unilateral sinus disease on initial imaging are less likely chronic rhinosinusitis compared to patients with bilateral disease. This should be taken into consideration in the workup and management of patients with unilateral sinus disease. Level of Evidence: 3 Laryngoscope, 130:E116–E121, 2020